Risk Factors of Surgical Site Infections in Cesarean Sections in Lady Reading Hospital Peshawar - Khan, Hafsa; Khattak, Saima; Habib, Amna (Indus Journal of Bioscience Research, 2025)
Background: Surgical site infections are a major source of morbidity following cesarean deliveries, increasing hospital stays, healthcare costs, and maternal discomfort. Identifying patient-related and clinical risk factors is crucial for early intervention and prevention, particularly in regions with limited healthcare resources. Objective: To determine the risk factors of surgical site infections in patients undergoing cesarean sections in Lady Reading Hospital Peshawar. Study Design: Cross-sectional study. Duration and Place of Study: The research was conducted in the Department of Obstetrics and Gynecology, Lady Reading Hospital, Peshawar, from July 2024 to December 2024. Methodology: A total of 177 women aged 18–40 years who developed surgical site infections after cesarean section were included. Sampling was performed using a non-probability consecutive technique. Risk factors assessed included prolonged rupture of membranes (>20 hours), preeclampsia, and meconium-stained amniotic fluid. Data were analyzed in SPSS version 25, with associations tested using Chi-square or Fisher’s exact test at a 5% significance threshold. Results: Prolonged rupture of membranes was observed in 26.0% of cases, preeclampsia in 19.2%, and meconium-stained liquor in 5.6%. Hypertension showed a strong association with preeclampsia (p